Studi Efektivitas Aplikasi Sistem Integrasi Sekretariat dan Unsur Penunjang (Si-SEKRUP) di Lingkungan Diskominfo Jawa Tengah - Hendri Prasetyo; Fitria Nur 'Aini (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
The development of information and communication technology (ICT) has encouraged the implementation of Electronic-Based Government Sistems (SPBE) aimed at improving the quality of public services to become more transparent, accountable, and efficient. In line with this, the Department of Communication and Informatics (Diskominfo) of Central Java Province developed the Integrated Secretariat and Supporting Unit Sistem (Si-SEKRUP) application as a digital innovation specifically designed to support internal administrative management. The presence of this application represents a concrete step in bureaucratic digital transformation, particularly in realizing administrative services that are fast, integrated, and oriented toward the principles of good governance. This study aims to evaluate the effectiveness of the Si-SEKRUP application in supporting digital-based administrative governance. The research method applied is descriptive qualitative, utilizing secondary data obtained from literature, official reports, and public documents, with validation through data triangulation. The findings show that the implementation of Si-SEKRUP has significantly improved administrative efficiency, as reflected in the acceleration of document processing by up to 50%, the achievement of 100% digital documentation, and a substantial reduction in paper use that supports a paperless office sistem. Furthermore, the integration of digital and real-time asset monitoring has enhanced organizational transparency and accountability. The implementation of this application has not only provided technical benefits but has also fostered a shift in employee work culture toward more adaptive, collaborative, and productive practices in line with digital-era demands. These findings affirm that the success of bureaucratic digital transformation requires sustainable development, both in terms of technological infrastructure and human resource competencies, so that SPBE utilization can run optimally and deliver tangible value to public services.